Evaluation of sclerotherapy for the treatment of infected postoperative lymphocele - Youdong Kim; Gyeong Sik Jeon; Sun Young Choi; Man Deuk Kim; Shin Jae Lee (Elsevier, 2017)
Objective: To evaluate the efficacy and safety of sclerotherapy as the treatment of infected postoperative lymphocele in gynecologic malignancy patients. Materials and methods: Percutaneous catheter drainage (PCD) with or without sclerotherapy was performed for postoperative lymphocele in 75 patients from 2002 to 2014. Eighty-eight lymphoceles (43 non-infected as group A, 45 infected as group B) in 75 patients (mean age ± SD; 50.3 ± 11.3) were included. Sclerotherapy was performed in 17 (39.5%, group A-S) lymphoceles in group A and 14 (31.1%, group B-S) in group B. Absolute ethanol was the most frequently used sclerosant (28 of total 36 sessions). Mean follow-up period was 37 months (range: 1-154). Results: Sclerotherapy was clinically successful in 13 lymphoceles in both group A-S (76.5%) and group B-S (92.9%) without statistical significance. Compared to the pre-sclerotherapy period, group B-S demonstrated significantly decreased drainage volume after sclerotherapy (662.7 ml vs. 100.6 ml, p = 0.019). Group A-S failed to demonstrate significant decrease in drainage volume after sclerotherapy. Recurrence occurred in 4 patients in group A-S and 1 in group B-S, without statistical significance. No major complication was noted. Conclusion: Sclerotherapy significantly reduces the drainage volume, and might help shorten catheter placement time in infected lymphoceles.